Sublevel open stoping : design of the O640, L651 and N659 sub-level open stopes in the 3000 orebody of the Mount ISA copper mines, Queensland, Australia - Handley, M.F. (University of Pretoria, 2013)
Dissertation (MEng)--University of Pretoria, 2011.